Trail of Tears : a Native American documentary collection. - Richie, Chip; Jones, James Earl; Howard, Gregg; Ross, Gayle; Studi, Wes (Minneapolis, MN : Mill Creek Entertainment, 2010)
Documents the forced removal in 1838 of the Cherokee Nation from the southeastern United States to Oklahoma; explores issues of racial identity between the mixed-descent peoples of both Native American and African American heritage; examines the crossover of ancient native remedies to present-day medical practices; documents the 1869, U.S. government-enacted policy of educating Native American children in the ways of western society.
Trail of Tears : Cherokee legacy (2006, 105 min.) / written by Daniel Blake Smith ; produced by Chip Richie, Steven R. Heape ; directed by Chip Richie -- Black Indians : an American story (2001, 52 min.) / written by Daniel Blake Smith ; directed by Chip Richie -- Native American healing in the 21st century (2004, 52 min.) / written by Howard Fisher ; produced and directed by Chip Richie -- Our spirits don't speak English : Indian boarding school (2008, 53 min.) / written by Dan Agent ; directed by Chip Richie.
Title from container.
Narrators: James Earl Jones (Trail of Tears, Black Indians), Gregg Howard (Native American healing in the 21st century), Gayle Ross (Our spirits don't speak English) ; Wes Studi, presenter (Trail of Tears).
"Black Indians" originally broadcast on television.
Rating: Not rated, TV-PG.
DVDs, Dolby digital stereo.
Keywords: Trail of Tears, 1838-1839.; Cherokee Indians -- Relocation; Cherokee Indians -- History -- 19th century; Cherokee Indians -- Government relations; Indians, Treatment of -- United States -- History -- 19th century; African Americans -- Relations with Indians; Indians of North America -- Mixed descent; Indians of North America -- Medicine; Indians of North America -- Ethnobotany; Indians of North America -- Education -- History; Off-reservation boarding schools -- United States; Discrimination in education -- United States -- History; Nonfiction films; Nonfiction television programs; Documentary television programs; Documentary films